Exercise elevates serum brain-derived neurotrophic factor in partially remitted depression - Kramer, Benedikt Alexander; Jähn, Anna; Grützner, Thea M.; Hess, Natalie Sarah; Bellanti, Amanda; Listunova, Lena; Hellweg, Rainer; Weisbrod, Matthias; Roesch-Ely, Daniela (Psychiatry research, 2023)
Brain-derived neurotrophic factor (BDNF) is a pleiotropic cytokine implicated in the pathogenesis of major depressive disorder (MDD). In MDD, serum BDNF levels are attenuated. Healthy adults show BDNF elevation after exercise. To investigate activity-dependent BDNF elevation in MDD, thirty-seven participants with partially remitted MDD were allocated to either a bout of strenuous or light activity. Serum was collected before and after the intervention. BDNF was measured using a highly sensitive and specific enzyme-linked immunosorbent assay. Significant BDNF elevation in the strenuous activity group emerged. This study confirms exercise-dependent serum BDNF elevation in MDD. Preregistration: German Clinical Trials Register (DRKS0001515).
Gesehen am 23.08.2023
Online verfügbar: 3 June 2023, Dokumentversion: 7 June 2023